Chinese Real Estate Market Risk Measure by Value-at-Risk: an Empirical Study on Real Estate Market of Beijing and Chongqing - Yang, Yunhan (2013)
Purpose – The purpose of this article is introducing a quantified risk assessment use in real estate for forecasting mark risks from a macro view, and applies it in real market to give suggestions for investors and government. Early studies of real estate investment market are focus on finance productions, such as property trust, real estate stocks. This article tries to outline the whole real estate industry’s risk level.